2018
DOI: 10.1017/jfm.2018.415
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation of a surfactant-laden drop under the influence of an electric field

Abstract: The sedimentation of a surfactant-laden deformable viscous drop acted upon by an electric field is considered theoretically. The convection of surfactants in conjunction with the the combined effect electrohydrodynamic flow and sedimentation leads to a locally varying surface tension, which subsequently alters the drop dynamics via the interplay of Marangoni, Maxwell and hydrodynamic stresses. Assuming small capillary number and small electric Reynolds number, we employ a regular perturbation technique to solv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 67 publications
(120 reference statements)
4
55
0
Order By: Relevance
“…The dynamics of a fluid drop in another immiscible fluid has been a topic of substantial research over many years owing to its large range of applications such as the science of colloids and emulsions (Meyyappan, Wilcox & Subramanian 1983;Zhang & Davis 1992), sedimentation (Rushton & Davies 1973;Haber & Hetsroni 1981;Poddar et al 2018), † Email address for correspondence: uddipta.ghosh@iitgn.ac.in early biomechanical modelling of cells (Hochmuth et al 1993;Tsai, Frank & Waugh 1993), to name but a few. A large number of studies have, therefore, been carried out focusing on various aspects of droplet motion (see for example, Hetsroni & Haber 1970;Haber & Hetsroni 1971;Rallison 1981;Acrivos 1983;Bentley & Leal 1986;Sherwood 1988;Subramanian & Balasubramanian 2001;Probstein 2005;Baroud, Gallaire & Dangla 2010;Lavrenteva, Rosenfeld & Nir 2011;Anna 2016), among which, settling of drops has received significant attention over the years (Vizika & Saville 1992;Ha & Yang 1995;Probstein 2005;Leal 2007;Poddar et al 2018), as attributable to its relevance in industrial applications, such as in crude-oil industries (Mhatre et al 2015;Mandal, Bandopadhyay & Chakraborty 2017a), various separation processes (Ptasinski & Kerkhof 1992) as well as in several other microfluidic applications. As such, various aspects of droplet sedimentation have been rigorously analysed over the years (Subramanian & Balasubramanian 2001;Anna 2016), which include dynamics of freely falling drops (Subramanian & Balasubramanian 2001;Probstein 2005;Leal 2007), influence of external electric fields on...…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of a fluid drop in another immiscible fluid has been a topic of substantial research over many years owing to its large range of applications such as the science of colloids and emulsions (Meyyappan, Wilcox & Subramanian 1983;Zhang & Davis 1992), sedimentation (Rushton & Davies 1973;Haber & Hetsroni 1981;Poddar et al 2018), † Email address for correspondence: uddipta.ghosh@iitgn.ac.in early biomechanical modelling of cells (Hochmuth et al 1993;Tsai, Frank & Waugh 1993), to name but a few. A large number of studies have, therefore, been carried out focusing on various aspects of droplet motion (see for example, Hetsroni & Haber 1970;Haber & Hetsroni 1971;Rallison 1981;Acrivos 1983;Bentley & Leal 1986;Sherwood 1988;Subramanian & Balasubramanian 2001;Probstein 2005;Baroud, Gallaire & Dangla 2010;Lavrenteva, Rosenfeld & Nir 2011;Anna 2016), among which, settling of drops has received significant attention over the years (Vizika & Saville 1992;Ha & Yang 1995;Probstein 2005;Leal 2007;Poddar et al 2018), as attributable to its relevance in industrial applications, such as in crude-oil industries (Mhatre et al 2015;Mandal, Bandopadhyay & Chakraborty 2017a), various separation processes (Ptasinski & Kerkhof 1992) as well as in several other microfluidic applications. As such, various aspects of droplet sedimentation have been rigorously analysed over the years (Subramanian & Balasubramanian 2001;Anna 2016), which include dynamics of freely falling drops (Subramanian & Balasubramanian 2001;Probstein 2005;Leal 2007), influence of external electric fields on...…”
Section: Introductionmentioning
confidence: 99%
“…The high voltage is supplied across the electrodes and dynamics are captured by using cameras. In these studies, some authors have also introduced surfactants at the liquid-liquid interface [ 27 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A summary of the most prominent works related to droplet EHD are summarized in Table 1 .…”
Section: Approaches Used To Study the Droplet Electrohydrodynamicsmentioning
confidence: 99%
“…The influence of interfacial properties on the droplet deformation and breakup under an electric field has also been a topic of profound interest for decades [ 27 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. The surface-active molecules prompt to change in the interracial and rheological properties, leading to interfacial perturbations and breakups [ 23 , 71 , 136 , 137 , 138 ].…”
Section: Surfactant-laden Dropletsmentioning
confidence: 99%
“…Motivated by the classical work of Taylor (1966), several studies have been reported on electrically modulated morpho-dynamics of droplets in an external flow (Hase, Watanabe & Yoshikawa 2006; Ristenpart et al 2009; Mhatre & Thaokar 2013; Zhang et al 2016; Brosseau & Vlahovska 2017; Poddar et al 2018, 2019 b ; Behera et al 2019; Santra et al 2018 b , 2019 a ; Santra, Das & Chakraborty 2020). Mandal, Bandopadhyay & Chakraborty (2016) studied the cross-stream migration of the droplet in unbounded plane Poiseuille flow under uniform electric field.…”
Section: Introductionmentioning
confidence: 99%